Az Észak-alföldi régió élelmiszerjellegű vegyes bolti kiskereskedelmi tevékenységet végző vállalkozásainak elemzése - Fenyves, Veronika; Tarnóczi, Tibor; Bács, Zoltán (Közép-Európai Közlemények, 2016)
The international food trade has undergone large changes horizontally and vertically during the past decades. Concentration is increasing worldwide with respect to hyper- and supermarkets, discount stores as well as wholesalers. Position of the Hungarian food retail trade fundamentally changed after the change of regime: the formerly state- and cooperative-owned retail units were replaced by units operating in private property as well as different commercial chains (being in domestic and foreign ownership) appeared in the sector. After the turn of the millennium, expansion of the commercial chains has accelerated and they have a significant market share now. The Hungarian food retail trade, like the European average, is characterized by a high concentration. Aim of our treatise is to examine how far the sector-specific high concentration can be observed in the financial statements of those enterprises of the Northern Great Plain region which are performing retail sale activity in non-specialised stores with food.